Photocatalyst film-bearing substrate and water-splitting device including the same

A substrate with a photocatalytic film, using a binder of Al and alkali metals, addresses the durability issue of photocatalytic particles, ensuring stable hydrogen production by preventing peeling and enhancing longevity in water cracking devices.

JP2025020018APending Publication Date: 2025-02-07NIPPON SHEET GLASS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024114427
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2024-07-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing hydrogen production technologies focus on improving photocatalytic particles but neglect the durability and stability of photocatalytic particles when fixed to a substrate, leading to potential peeling during water cracking operations.

Method used

A substrate with a photocatalytic film is developed, incorporating photocatalyst particles and a binder, where the binder includes at least one metal element from Al and alkali metals to enhance adhesion, and the film is tested for durability through a warm water immersion process.

Benefits of technology

The substrate with a photocatalytic film provides stable hydrogen production by preventing peeling and ensuring longevity, making it suitable for continuous water cracking operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020018000001_ABST
    Figure 2025020018000001_ABST
Patent Text Reader

Abstract

To improve a photocatalyst film-bearing substrate for use in a water-splitting device.SOLUTION: A photocatalyst film-bearing substrate 10 includes a substrate 1 and a photocatalyst film 2 formed on the substrate 1. The photocatalyst film 2 includes photocatalyst particles, which can exhibit photocatalytic activity to produce gas from water upon light irradiation, and a binder in contact with the photocatalyst particles. The photocatalyst film 2 does not peel off from the substrate 1 even after being subjected to a hot water immersion test, where the hot water immersion test is performed by keeping the photocatalyst film-bearing substrate 10 submerged in water at 40°C for four days.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a substrate with a photocatalyst film, and further to a water splitting device using the substrate with a photocatalyst film. [Background technology]

[0002] Hydrogen production technology that splits water using photocatalysts has been attracting attention. This is because hydrogen production technology that directly splits water using light energy can be a technology for supplying inexpensive hydrogen on a large scale. Various photocatalyst particles have been developed to pursue this possibility. For example, Non-Patent Document 1 discloses a photocatalyst in which a co-catalyst is selectively introduced into a specific crystal face of Al-doped SrTiO3 particles. This photocatalyst particle makes it possible to split water with a quantum yield of almost 100% and generate hydrogen and oxygen. In addition, Patent Document 1 discloses photocatalyst particles in which a co-catalyst different from that in Non-Patent Document 1 is supported on Al-doped SrTiO3 particles. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] Nature, 2020, vol.581, pp.411-414 [Patent documents]

[0004] [Patent Document 1] JP 2023-88059 A Summary of the Invention [Problem to be solved by the invention]

[0005] So far, the main focus of development in hydrogen production technology has been on improving photocatalyst particles. On the other hand, as far as the inventors know, little research has been done on the technology of fixing photocatalyst particles to a substrate. Therefore, the present invention aims to provide a new photocatalyst film-coated substrate that can become a key device in water splitting equipment. [Means for solving the problem]

[0006] In order to stably supply hydrogen, it is desirable to extend the usable period of a water splitting apparatus. As a result of investigations from the viewpoint of extending the usable period, the present inventors found that there was room for improvement in the durability of a photocatalyst film-coated substrate that is continuously exposed to water and generated gas during the operation of a water splitting apparatus, and thus completed the present invention.

[0007] The present invention relates to A substrate and a photocatalytic film formed on the substrate, The photocatalyst film includes photocatalyst particles capable of exerting a photocatalytic action of generating gas from water upon irradiation with light, and a binder in contact with the photocatalyst particles, A substrate with a photocatalyst film is provided, in which the photocatalyst film does not peel off from the substrate after a warm water immersion test is performed. However, the warm water immersion test is a test in which the photocatalyst film-attached substrate is immersed in water at 40° C. for 4 days.

[0008] From another aspect, the present invention provides A substrate and a photocatalytic film formed on the substrate, The photocatalyst film includes photocatalyst particles capable of exerting a photocatalytic action of generating gas from water upon irradiation with light, and a binder in contact with the photocatalyst particles, The binder contains at least one metal element selected from the group consisting of Al and alkali metal elements, providing a substrate with a photocatalyst film.

[0009] The present invention also provides a water splitting device comprising the photocatalyst film-coated substrate of the present invention. Effect of the Invention

[0010] According to the present invention, there are provided a photocatalyst film-coated substrate and a water splitting apparatus suitable for stably supplying inexpensive hydrogen. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a cross-sectional view showing an example of a substrate with a photocatalyst film. [Diagram 2] FIG. 1 is a partial cross-sectional view showing an example of a water splitting apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will now be described in detail, but the following description is not intended to limit the present invention to a specific embodiment.

[0013] The present invention provides a photocatalyst film-coated substrate and a water splitting apparatus having the following configurations. The first form is, A substrate and a photocatalytic film formed on the substrate, The photocatalyst film includes photocatalyst particles capable of exerting a photocatalytic action of generating gas from water upon irradiation with light, and a binder in contact with the photocatalyst particles, The photocatalyst film-attached substrate is one in which the photocatalyst film does not peel off from the substrate after a warm water immersion test is performed. However, the warm water immersion test is a test in which the photocatalyst film-attached substrate is immersed in water at 40° C. for 4 days.

[0014] A second embodiment is the photocatalyst film-attached substrate according to the first embodiment, wherein the binder contains at least one metal element selected from the group consisting of Al and alkali metal elements.

[0015] In addition, the first form is, A substrate and a photocatalytic film formed on the substrate, The photocatalyst film includes photocatalyst particles capable of exerting a photocatalytic action of generating gas from water upon irradiation with light, and a binder in contact with the photocatalyst particles, The binder may be a substrate with a photocatalyst film, which contains at least one metal element selected from the group consisting of Al and alkali metal elements.

[0016] A third embodiment is the photocatalyst film-attached substrate according to the second embodiment, wherein the binder contains Al.

[0017] A fourth aspect is the photocatalyst film-attached substrate according to the second or third aspect, wherein the binder further contains Si.

[0018] A fifth aspect is the photocatalyst film-attached substrate according to any one of the first to fourth aspects, wherein the binder contains non-spherical particles.

[0019] A sixth embodiment is the substrate with a photocatalyst film according to the fifth embodiment, wherein the non-spherical particles have a ratio of the major axis L1 to the minor axis L2 of 10 or more.

[0020] A seventh aspect is the photocatalyst film-attached substrate according to the fifth or sixth aspect, wherein the non-spherical particles are non-spherical particles derived from a feathery metal oxide sol.

[0021] An eighth embodiment is the photocatalyst film-attached substrate according to any one of the fifth to seventh embodiments, wherein the binder further contains spherical particles.

[0022] In the ninth embodiment, the photocatalytic film is 100 m 2 / g or more.

[0023] A tenth aspect is the photocatalyst film-attached substrate according to any one of the first to ninth aspects, wherein the substrate includes a glass plate or glass fiber.

[0024] An eleventh embodiment is a water splitting device comprising the photocatalyst film-coated substrate according to any one of the first to tenth embodiments.

[0025] [Photocatalytic film-coated substrate] Fig. 1 shows a cross section of an example of a photocatalyst film-coated substrate of this embodiment. The photocatalyst film-coated substrate 10 includes a substrate 1 and a photocatalyst film 2 formed on the substrate 1. The photocatalyst film 2 contains photocatalyst particles and a binder. The substrate and the photocatalyst particles and binder contained in the photocatalyst film will be described below.

[0026] (Base) The substrate has a function of supporting the photocatalytic film, and as long as it can perform this function, there is no limitation on its shape and material. The shape of the substrate is, for example, plate-like or container-like. The plate-like substrate may be a flat plate or a curved plate. The substrate may contain at least one selected from the group consisting of metal, resin, and inorganic compound. Specifically, the substrate may contain a resin material or a glass material, or may contain a glass material. The substrate may contain a glass plate or glass fiber. The substrate containing glass fiber may be a molded body of glass fiber, represented by glass mat and glass cloth. When the substrate contains a glass material that is prone to peeling of the photocatalytic film, the application of this embodiment makes it easy to obtain a remarkable effect in preventing peeling. There is also no particular limitation on the thickness of the substrate. The substrate may have a base film on the surface on which the photocatalytic film is formed. The base film may be a single-layer film, or a multi-layer film having two or more layers.

[0027] (Photocatalyst particles) The photocatalyst particles exert a photocatalytic function of generating gas from water upon receiving light irradiation. The generated gas may contain at least one selected from the group consisting of hydrogen and oxygen. The photocatalyst particles may have a photocatalytic function of decomposing water upon receiving light irradiation to generate hydrogen and oxygen. However, the photocatalyst particles may contain first photocatalyst particles that generate hydrogen and second photocatalyst particles that generate oxygen. The system including the first photocatalyst particles and the second photocatalyst particles may contain a medium responsible for charge transfer. In the system including the medium responsible for charge transfer, the first photocatalyst particles generate hydrogen from water upon receiving light irradiation, and oxidize the medium to generate an oxidized form. The second photocatalyst particles generate oxygen upon receiving light irradiation, and reduce the medium to generate a reduced form. The reduced form becomes an oxidized form by an oxidation reaction involving the first photocatalyst particles, and returns from an oxidized form to a reduced form by a reduction reaction involving the second photocatalyst particles.

[0028] The photocatalyst particles may include at least one compound selected from the group consisting of oxides, oxynitrides, nitrides, and chalcogenide compounds. The photocatalyst particles may include at least one element selected from the group consisting of Sr, Na, Mg, Al, Si, Ca, Ti, V, Fe, Cu, Zn, Ga, Y, Zr, Nb, Ag, In, Sn, Ba, La, Ta, W, and Bi.

[0029] The compounds contained in the photocatalyst particles may be doped, and in some cases, a co-catalyst may be introduced to enhance the photocatalytic function. For example, SrTiO3 may be doped with Al (SrTiO3:Al), or co-doped with Rh and Sb (SrTiO3:Rh,Sb). For example, SrTiO3:Al may support Rh / Cr2O3 as a hydrogen generation co-catalyst and CoOOH as an oxygen generation co-catalyst (Non-Patent Document 1). However, the co-catalyst for SrTiO3:Al is not limited to the above, and may be, for example, a co-catalyst containing Co and Cr, and Ru and / or Pt (Patent Document 1).

[0030] The influence of the doping material and the co-catalyst on the adhesion between the photocatalyst film and the substrate is extremely limited. In the following description, the types of dopants and co-catalysts will be omitted and the photocatalyst particles will be described. For example, the photocatalyst particles and the photocatalyst materials disclosed in Non-Patent Document 1 and Patent Document 1 will be described as "SrTiO3 particles" and "SrTiO3", respectively.

[0031] The photocatalytic material contained in the photocatalytic particles can be various compounds sometimes called optical semiconductors. The photocatalytic material is irradiated with, for example, ultraviolet light or visible light to generate photoexcited charges, which reduce protons on the particle surface to generate hydrogen or oxidize water molecules to generate oxygen. Examples of the photocatalytic material include SrTiO3, Y2Ti2O5S2, BaTa2O5, BaTaO2N, BaLa4Ti4O 15 , NaTaO3, AgTaO3, AgLi 1 / 3 Ti 2 / 3 O2, Ga2O3, WO3, (Cu,Ga) 0.8 Zinc 0.4 S2, CuGaS2, LaMg 1 / 3 Ta 2 / 3 The photocatalytic material may include at least one selected from the group consisting of O2N, SnNb2O6, NaNbO3, Ta3N5, Sn3O4, BiVO4, Bi2MoO6, PbMO4, PbWO4, AgVO3, Ag3VO4, and La2Ti2O7. The photocatalytic material may be a composite material. For example, La2Ti2O7 may be a material composited with black phosphorus and gold nanoparticles.

[0032] The average particle size r1 of the photocatalyst particles may be, for example, in the range of 100 nm to 3 μm, or even 200 nm to 1 μm. The average particle size can be determined by arithmetic average of the particle sizes of 50 particles, which are arbitrarily selected when observed with a scanning electron microscope, and the average value of the maximum length (major axis) L1 that can be secured within each particle and the length (minor axis) L2 of the granular body along the axis perpendicular to the midpoint of the major axis is taken as the particle size of the selected particle. Photocatalyst particles having an average particle size of 100 nm or more, or even 200 nm or more, tend to peel off easily from the substrate.

[0033] (Binder) The binder has a function of suppressing peeling of the photocatalytic film from the substrate. At least a part of the binder is in contact with the photocatalytic particles and can contribute to the fixation of the photocatalytic particles. The binder may contain at least one metal element selected from the group consisting of Al, Ta, Nb, Ce, Fe, and alkali metal elements. The alkali metal element may be at least one selected from the group consisting of Li, Na, and K. The binder may particularly contain Al and / or an alkali metal element. The binder may further contain Si as an element together with the at least one metal element described above, particularly Al and / or an alkali metal element. The binder may contain an inorganic compound such as an oxide, an oxynitride, or a nitride, particularly an oxide. However, without being limited thereto, the binder may contain an organic compound represented by cellulose nanofiber, or may contain a carbon element represented by carbon nanotube, fullerene, and graphene. The binder may contain glass fiber.

[0034] The form of the binder is not particularly limited, and may be granular. However, the binder may be amorphous instead of granular. Granular binders are derived from, for example, a sol contained in a coating liquid for forming a photocatalyst film. Amorphous binders are derived from, for example, metal alkoxides, alkali silicates, etc. in the coating liquid.

[0035] An example of the shape of the granular body is a sphere. In this specification, a spherical particle means a shape in which, when observed with an electron microscope such as a scanning electron microscope, the major axis of the granular body (the maximum length that can be secured within the granular body) is L1 and the length of the granular body along an axis perpendicular to the midpoint of the major axis (minor axis) is L2, L1 / L2<3 holds. Therefore, cubic particles are treated as spherical particles in this specification.

[0036] The shape of the granular body may be non-spherical. In this specification, the non-spherical particle means a shape in which L1 / L2≧3 is satisfied based on the above-mentioned L1 and L2 when observed with an electron microscope such as a scanning electron microscope. In the non-spherical particle, L1 / L2≧5, L1 / L2≧10, and even Li / L2≧15 may be satisfied. Examples of the shape of the non-spherical particle include a rod shape having a needle shape, a columnar shape, etc.; a chain shape in which granular bodies are connected in a chain shape; a fiber shape; and a feather shape in which a plurality of fibrous bodies are aggregated in a feather shape. The non-spherical particle may be at least one selected from the group consisting of rod-shaped particles, chain-shaped particles, fibrous particles, and feather-shaped particles. A relatively high effect of suppressing peeling of the photocatalyst film can be obtained from the non-spherical particles. The non-spherical particles can be introduced into the photocatalyst film using, for example, a sol containing the non-spherical particles.

[0037] The average particle size r2 of the granular binder may be, for example, in the range of 10 nm to 50 nm, or even 30 nm to 50 nm. As explained for the average particle size r1 of the photocatalyst particles, the average particle size can be determined by the average particle size of 50 granules, with the average value of the long axis L1 and the short axis L2 of the granule being the particle size of the granule. The average particle size r2 of the binder may be smaller than the average particle size r1 of the photocatalyst particles (r1>r2).

[0038] The average major axis of the binder, which is a non-spherical particle, may be, for example, in the range of 100 nm to 5 μm, or further in the range of 100 nm to 3 μm. The average minor axis of the binder, which is a non-spherical particle, may be, for example, in the range of 1 nm to 20 nm, or further in the range of 3 nm to 10 nm. The average major axis may be in the range of 5 to 5000 times, or further in the range of 10 to 100 times, the average minor axis. The average major axis and the average minor axis, like the average particle size, can be determined by arbitrarily selecting 50 particles and averaging the major axis L1 and the minor axis L2 of each particle when observed with a scanning electron microscope.

[0039] It is preferable that at least a part of the binder is granular. Granular materials are relatively advantageous in terms of securing voids around the photocatalyst particles. In particular, when using an amorphous binder containing an alkali metal element, it is preferable to use a granular binder in combination.

[0040] (Ratio of photocatalyst particles to binder / Ratio of binder) In the photocatalyst film, the ratio of the photocatalyst particles to the binder may be in the range of 99:1 to 20:80, 99:1 to 50:50, or 97:3 to 50:50 by mass. The ratio of the photocatalyst particles to the binder may be in the range of 90:10 to 60:40. However, from the viewpoint of ensuring the amount of gas generated from the photocatalyst particles, the ratio of the photocatalyst particles to the binder may be in the range of 99:1 to 80:20, 97:3 to 80:20, or even 95:5 to 80:20.

[0041] The binder may include a binder A containing Al and / or an alkali metal element and a binder B containing Si. In this case, the ratio of the binder A to the binder B may be in the range of 90:10 to 5:95, or further 90:10 to 10:90, based on mass. The ratio of the binder A to the binder B may be in the range of 40:60 to 5:95, or further 30:70 to 5:95, based on mass. The ratio of the binder C, which is a non-spherical granular body, to the binder D, which is a spherical granular body, may also be in the range of the ratio described for the binders A and B, based on mass. The ratio of the binder C to the binder D is, for example, in the range of 40:60 to 5:95, or further 30:70 to 5:95.

[0042] The mass of the binder in the photocatalyst film can be determined based on the compounds (e.g., Al2O3, Li2O, SiO2) of the target elements (e.g., metal elements such as Al, Li, Na, and metalloid elements such as B and Si) in the photocatalyst film.

[0043] (Photocatalytic film thickness) The thickness of the photocatalyst film is not particularly limited, but is, for example, 1 μm or more, further 2 μm or more, and 20 μm or less, further 15 μm or less.

[0044] (Adhesion of photocatalyst film) The adhesion of the photocatalyst film to the substrate can be evaluated by a hot water immersion test. Photocatalyst films that generate gas from water are used while immersed in water, so an index of durability can be obtained by evaluating the adhesion in this state. The hot water immersion test is performed by immersing the substrate with the photocatalyst film in water at 40°C and leaving it to stand for four days. This test takes into account the fact that the water in the water splitting device may rise in temperature due to exposure to light such as sunlight.

[0045] (Specific surface area of ​​photocatalyst film) From the viewpoint of securing a portion for generating gas, it is desirable for the photocatalyst film to have a high specific surface area. For example, the specific surface area of ​​the photocatalyst film is 50 m 2 / g or more, 80m 2 / g or more, and 100m 2 / g or more, in some cases 120m 2 The upper limit of the specific surface area is not particularly limited, but may be, for example, 1000 m 2 / g or less, and 500m 2 / g or less. The photocatalyst film may be a porous film having the above-mentioned specific surface area. The specific surface area of ​​the photocatalyst film can be measured by the method described later.

[0046] (Method of manufacturing a substrate with a photocatalyst film) The substrate with a photocatalyst film can be produced by a method including applying a coating liquid for forming a photocatalyst film to a substrate. The solid content in the coating liquid may be, for example, 18% or more, 20% or more, or even 35% or more by mass. The upper limit of the solid content may be 40% or less. An appropriate solid content concentration ensures the homogeneity of the film and suppresses a decrease in the adhesion of the film. This method may further include heating the substrate to which the coating liquid has been applied. The heating temperature is preferably 100 to 350°C.

[0047] [Water splitting equipment] FIG. 2 shows a cross section of an example of the water splitting device of this embodiment. The water splitting device includes a support 11, a light-transmitting body 12, and a sealant 13 that seals a gap 18 between the support 11 and the light-transmitting body 12 in a water-tight manner. The gap 18 is surrounded by the support 11, the light-transmitting body 12, and the sealant 13, and communicates with the outside through two holes 16 and 17. The photocatalyst film-attached substrate 10 is disposed on the support 11 so that the film surface of the photocatalyst film 2 is exposed to the gap 18. The two holes, that is, the water inlet hole 16 and the gas outlet hole 17, are provided in the light-transmitting body 12. However, this is not limited to this, and the holes 16 and 17 can also be provided in other positions that communicate the gap 18 with the outside of the device. As shown in the figure, when light 20 is irradiated in a state in which water is introduced into the gap 18 from the hole 16, the water in contact with the photocatalyst film is decomposed to generate gas 19, and the gas 19 is discharged from the hole 17. EXAMPLES

[0048] The present invention will now be described more specifically with reference to examples and comparative examples. (Comparative Examples 1 to 7 and Examples 1 to 14) A coating liquid containing photocatalyst particles was prepared. As the photocatalyst particles, SrTiO3 particles with an average particle size of 300 nm were used. Various oxide sols were blended into the coating liquid to supply a binder, except for Comparative Example 1. The solid content concentration in the coating liquid was controlled within the range of 18 to 20 mass %. The mass ratio of the photocatalyst particles and binder constituting the solid content was adjusted as shown in Table 1. In Tables 1 and 3, the binders are classified into binders other than silicon oxide (specifically, titanium oxide, zirconium oxide, niobium oxide, and aluminum oxide) and silicon oxide binders.

[0049] The coating liquid was applied to the surface of the glass plate using a bar coater. A float glass plate with a thickness of 3 mm was used. The bar coat was performed so that the thickness of the applied liquid was about 20 μm. After applying the coating liquid, the glass plate was air-dried for 10 minutes and further heated at 150° C. for 45 minutes. In this way, a glass plate with a photocatalyst film was obtained.

[0050] (Examples 15 to 17) A glass plate with a photocatalyst film was obtained in the same manner as above, except that silica sol was used as the oxide sol and lithium silicate was added as the alkali silicate. The solid content concentration in the coating liquid was 18 to 20 mass%. Lithium silicate is a liquid, not a sol, and becomes an amorphous oxide binder after film formation. In Table 2, the mass of lithium silicate is specifically calculated by converting lithium silicate into an oxide, specifically, Li and Si into Li2O and SiO2, and the total is the total. In addition to this total, the solid content concentration in Table 2 is calculated based on the photocatalyst particles and the solid content in the silica sol.

[0051] (Comparative Examples 8 to 10, Examples 18 to 20) A glass plate with a photocatalyst film was obtained in the same manner as above, except that the solid content concentration in the coating liquid was 15, 25, 30 or 40 mass%. The mass ratio of the photocatalyst particles and the oxide sol constituting the solid content was adjusted as shown in Table 3.

[0052] The raw materials of the binders used in the examples and comparative examples are as follows. The shape of the granules contained in the raw materials is given in parentheses immediately after the sol name.

[0053] [Oxide sol] <Binders other than silicon oxide> (Aluminum Oxide) Alumina sol (spherical): Nissan Chemical Co., Ltd. 520-A (other than Comparative Examples 8 to 10) Alumina sol (spherical): Bailar Al-L7 manufactured by Taki Chemical Industry Co., Ltd. (Comparative Examples 8 to 10) Alumina sol (feathered): Nissan Chemical AS-200 Alumina sol (rod-shaped): Kawaken Fine Chemicals Co., Ltd. 10A Alumina sol (fibrous): Kawaken Fine Chemicals F1000 (Titanium Oxide) Titania sol (spherical): Ishihara Sangyo Kaisha, Ltd. STS-01 (Zirconium oxide) Zirconia sol (spherical): ZSL-20N manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd. (Niobium oxide) Niobium oxide sol (spherical): Bailar Nb-G6000 manufactured by Taki Chemical Co., Ltd. <Silicon oxide binder> (Silicon oxide) Silica sol (spherical): Fuso Chemical Co., Ltd. PL-3H

[0054] [Alkaline silicate] Lithium silicate: Nissan Chemical Lithium silicate 35

[0055] "AS-200" contains feather-like aluminum oxide particles with a short diameter of 3-5 nm and a long diameter of 200-500 nm. "10A" contains columnar aluminum oxide particles with a diameter of 10 nm and a height of 50 nm. "F1000" contains fibrous aluminum oxide particles with a diameter of 4 nm and a length of about 1400 nm. The average particle size of the granular material contained in the spherical oxide sol is smaller than the average particle size of the photocatalyst particles, about 30-50 nm. However, "PL-3H" contains associated silicon oxide fine particles, and the primary particle size of the silicon oxide fine particles is 35 nm, the secondary particle size is 70 nm, and the degree of association is 2.7. In addition, the SiO2 / Li2O (molar ratio) of "Lithium Silicate 35" is 3.2-3.8.

[0056] (Hot water immersion test) A hot water immersion test was carried out on each of the photocatalyst film-coated substrates obtained from the above Examples and Comparative Examples to evaluate the film adhesion. The hot water immersion test was a test in which the photocatalyst film-coated substrate was immersed in water at 40°C for 4 days. The water temperature during the test was maintained at 40°C. The film adhesion was evaluated according to the following criteria. A: After the test, the membrane was not peeled off visually, and the nonwoven fabric (Ozu Sangyo, Bencot, contact area 4 cm) with a load of 100 g was 2 ) the film will not peel off even if the surface is wiped with B: After the test, the membrane was not peeled off visually, and the nonwoven fabric (Ozu Sangyo, BEMCOT, contact area 4 cm) with a load of 100 g was 2 ) to wipe the surface of the film, which will cause the film to peel off. C: At least a part of the film was peeled off visually after the test. D: At least a part of the film was peeled off before the test.

[0057] (specific surface area) The specific surface area of ​​the photocatalyst film on the substrate with the photocatalyst film was measured. The nitrogen adsorption method (BET method) was used for the measurement under the following conditions. The equipment used was a MicrotrackBell "BELSORP-miniII". For pretreatment, a MicrotrackBell "BELSORP-vacII" was used. The measurement subject was the photocatalyst film powder peeled off from the substrate. Pretreatment: 120℃ for 8 hours in vacuum Measurement method: Constant volume method ·Adsorption temperature: 77K Saturated vapor pressure: Actual measurement ·Adsorbent cross section: 0.162nm 2 Nitrogen balance waiting time: 500 seconds

[0058] [Table 1]

[0059] Aluminum oxide is suitable as a binder to improve the adhesion of the film, and the use of non-spherical particles is more suitable for improving the adhesion of the photocatalyst film than the use of spherical particles.

[0060] The specific surface area is 129 m for Examples 7 and 8, respectively. 2 / g, 142m 2 / g. Thus, the specific surface area of ​​the film showed a tendency to increase with an increase in the ratio of spherical particles. A film containing both spherical particles and non-spherical particles is suitable for improving the adhesion and specific surface area of ​​the film. The thickness of the photocatalyst film in Examples 5 and 7 was 4 μm.

[0061] [Table 2]

[0062] The binder derived from alkali silicate is suitable as a binder that improves the adhesion of the film. In Examples 15 to 17, the binder derived from alkali silicate (Li2O and SiO2) is about 87.5% SiO2 and about 12.5% ​​Li2O on a mass basis.

[0063] [Table 3]

[0064] When Table 3 is referred to together with Table 1 in which the solid content concentration is set to 18 to 20 mass%, it can be understood that the solid content concentration in the coating liquid may affect the adhesion of the photocatalytic film formed from the liquid. When the substrate with the photocatalytic film produced in the same manner as in Example 8 was immersed in water and exposed to sunlight, it was confirmed that hydrogen and oxygen were generated from the photocatalytic film. [Explanation of symbols]

[0065] 1 Base 2 Photocatalytic membrane 10. Substrate with photocatalytic film

Claims

1. A substrate and a photocatalytic film formed on the substrate, The photocatalyst film includes photocatalyst particles capable of exerting a photocatalytic action of generating gas from water upon irradiation with light, and a binder in contact with the photocatalyst particles, A substrate with a photocatalyst film, in which the photocatalyst film does not peel off from the substrate after a hot water immersion test is performed. The warm water immersion test is a test in which the photocatalyst film-coated substrate is immersed in water at 40° C. for 4 days.

2. 2. The substrate with a photocatalyst film according to claim 1, wherein the binder contains at least one metal element selected from the group consisting of Al and alkali metal elements.

3. The substrate with a photocatalyst film according to claim 2 , wherein the binder contains Al.

4. The substrate with a photocatalyst film according to claim 2 , wherein the binder further contains Si.

5. The substrate with a photocatalyst film according to claim 1 , wherein the binder contains non-spherical particles.

6. 6. The substrate with a photocatalyst film according to claim 5, wherein the non-spherical particles have a ratio of a major axis L1 to a minor axis L2 of 10 or more.

7. 6. The substrate with a photocatalyst film according to claim 5, wherein the non-spherical particles are non-spherical particles derived from a feathery metal oxide sol.

8. The substrate with a photocatalyst film according to claim 5 , wherein the binder further contains spherical particles.

9. The photocatalytic film is 100 m 2 The substrate with a photocatalyst film according to claim 1 , having a specific surface area of ​​at least 100 nm / g.

10. The substrate with a photocatalyst film according to claim 1 , wherein the substrate comprises a glass plate or a glass fiber.

11. A water splitting device comprising the photocatalyst film-coated substrate according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Photocatalyst for water decomposition

    JP2023088059A